2012
DOI: 10.1177/0218492312439310
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in thoracic actinomycosis

Abstract: Diagnosis of actinomycosis can be problematic because of difficulty in isolating actinomyces. In these cases, surgery is very helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…Choi et al [10] reported a 100% cure rate in 26 cases without recurrence, despite a relatively short follow-up duration (median 23 months). Possible explanations for treatment failure are drug-resistant co-pathogens and poor penetration of the drug caused by avascularity and induration of the infected area [14]. Although reported antimicrobial susceptibility tests indicate that most Actinomyces are susceptible to penicillin and amoxicillin, Actinomyces may acquire antibiotic resistance during antibiotic treatment [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [10] reported a 100% cure rate in 26 cases without recurrence, despite a relatively short follow-up duration (median 23 months). Possible explanations for treatment failure are drug-resistant co-pathogens and poor penetration of the drug caused by avascularity and induration of the infected area [14]. Although reported antimicrobial susceptibility tests indicate that most Actinomyces are susceptible to penicillin and amoxicillin, Actinomyces may acquire antibiotic resistance during antibiotic treatment [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Transbronchial or open lung biopsies are often in order to make the diagnosis. With the propensity of actinomycosis to mimic malignancy, diagnosis is often made after surgical resection [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Relapse is common, but with treatment, long-term prognosis is good. The combination of surgery plus antibiotics has been shown in small trials to prevent relapse [3, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…Także badania inwazyjne, jak biopsja bronchoskopowa, przezoskrzelowa biopsja płuca czy przezskórna biopsja cienkoigłowa lub gruboigłowa mają małą czułość, nawet mimo powtarzania. Stąd w zdecydowanej większości przypadków rozpoznanie promienicy, podobnie jak u tego chorego, jest rozpoznaniem histologicznym z pobranego wycinka drogą chirurgicznej biopsji płuca i przez niektórych autorów uznawane jest za "złoty standard" diagnostyczny [11,12].…”
Section: Dyskusjaunclassified